Pengaruh Pemberian Tepung Maggot Bsf Terhadap Bobot Potong, Bobot Karkas, Dan Persentase Karkas Burung Puyuh Umur 8 Minggu - Siregar, Magdalena; Tumanggor, Santa (LPPM Universitas HKBP Nommensen, 2022)
This study aims to determine the effect of BSF maggot flour on slaughter weight, carcass weight and carcass percentage of quail (Cortunix-cortunix japonica) aged 8 weeks. This research was conducted in Simalingkar A, Medan Tuntungan District. This study used 80 quails which were taken as many as 4 randomly from each treatment plot. At 8 weeks of age. The rations used were a mixture of several of feed prepared. The method used in this study was a Completely Randomized Design (CRD) which consisted of 5 treatments, namely P0 = 0% ; P1 = 5% ; P2 = 10% ; P3 = 15% dan P4 = 20% and each had 4 replications, each replication consisted of 10 quails. Parameters measured were slaughter weight, carcass weight and carcass percentage. The data obtained from the results of this study were analyzed by ANOVA. The conclusion obtained from the results of this study showed that the provision of BSF maggot flour in the ration had no significant effect (P>0.05) on slaughter weight, carcass weight. and carcass percentage of quail aged 8 weeks.